Regional Anestesi Subarachnoid Block pada Wanita 34 Tahun G2P1A0 Hamil Preterm, Pre Eklamsia Berat, Ketuban Pecah Dini 18 Jam, Pro SCTP dengan Status Fisik Asa II E - Soepraptomo, RTH (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2020)
Preeclampsia is still one of the leading causes of maternal and fetal death worldwide with an incidence of 5-14% of all pregnancies. Sectio caesarea is generally performed if there are certain medical indications, as an act of ending a pregnancy with complications. One indication of a caesarean section is severe preeclampsia. Many delivery procedures in health services have used regional anesthesia in its implementation, both epidural and spinal, because in addition to the mother being able to consciously experience the birth process, it also has lower morbidity and mortality rates than general anesthesia. On February 14, 2019, a 34-year-old woman came to the emergency room of RSDM with a gestational age of 34 + 6 weeks, G2P1A0 referral to Pandan Arang Hospital, Boyolali with information on PEB and Premature rupture of membrane (PROM) (18 hours) in preterm pregnant secundigravida with renal insufficiency + hypoalbumin not yet in labor. In this patient, cesarean section was performed with subarachnoid regional anesthesia technique.